Validation of TRF-E as gasoline surrogate through an experimental laminar burning speed investigation. (1st October 2019) - Di Lorenzo, M.; Brequigny, P.; Foucher, F.; Mounaïm-Rousselle, C.
Abstract: Nowadays, one of the main challenge in the automotive sector concerns the increase of Internal Combustion Engine efficiency. Present and future stringent standards call for reduction of fuel consumption and cut of pollutant emissions. In this respect, one technical solution is the downsizing of the engines that consists in increasing the intake pressure and temperature, through a turbocharger, while reducing the displacement. To avoid abnormal combustion occurrences, the use of high dilution rates is required. It is evident that due to these drastic constraints, high pressure and high dilution, the propagation and the stability of the premixed turbulent flame are strongly affected. Beyond this case, the laminar flamelet regime concept remains the base for the models used in industrial applications. Therefore, the knowledge of laminar burning speed is still crucial and an open research topic. As this parameter is dependent of fuel, its investigation is fundamental in order to evaluate potential suitable surrogates or/and alternative fuels. The present study aims to validate the TRF-E (a Toluene Reference Fuel blended with 5%vol ethanol) as suitable surrogate of a commercial gasoline and to gather a wide laminar burning velocities database for the TRF-E. For that, the laminar flame propagation inside a spherical stainless steel vessel was observed via a Double-View Schlieren technique. The temperature was set at 373, 423 and 473 K, while pressure and dilution were, respectively, 0.1, 0.2, 0.3 and 0.5 MPa and 0, 10 and 20%, for equivalence ratio range from 0.8 to 1.3. Thanks to this large laminar burning velocity database, it was possible to determine coefficients from the mathematical correlation proposed by Metghalchi and Keck (1982) with high precision by solving a global optimization problem. Reference conditions were fixed at 473 K, 0.1 MPa and 0% of dilution. In this case, the laminar burning velocity difference between TRF-E and gasoline is less than 4%. But the decrease of temperature and the increase of pressure or dilution affect the laminar burning velocity of these two fuels in a different way. Anyway, this gap is limited to 10–15% in the worst cases, confirming that TRF-E may be considered as a suitable surrogate of the investigated gasoline.